Case report: Thyroid sarcoidosis as a rare localization of the disease: Report of two cases and review of the literature - Kašiković Lečić, Svetlana; Javorac, Jovan; Lovrenski, Aleksandra; Đokić, Jelena; Sazdanić Velikić, Danica; Živanović, Dejan (Frontiers in Medicine, 2023)
Sarcoidosis is a multi-systemic disease of unknown etiology that is characterized by the formation of non-necrotizing and non-caseating granulomas in affected organs. Sarcoidosis granulomas can form in any organ, but the lungs and intrathoracic lymph nodes are the most commonly affected. Thyroid involvement in sarcoidosis is very rare, with prevalence estimates of 1–4.5% in case series of autopsied patients with systemic sarcoidosis. It is extremely rare for sarcoidosis to occur solely in the thyroid gland, but it is usually associated with the involvement of other organs, primarily the lungs and lymph nodes. Typical manifestations are diffuse goiter and solitary or multiple thyroid nodules. Thyroid function remains intact in the majority of cases, but sometimes it can result in hypothyroidism or hyperthyroidism. The diagnosis can be made after fine needle aspiration cytology, but usually it is diagnosed as an incidental finding while analyzing thyroidectomy tissue or during autopsy. Oral steroids are the cornerstone of thyroid sarcoidosis management, along with specific endocrinological treatment on some occasions. Given that we found only 71 reports of thyroid sarcoidosis available in the literature, we created and analyzed a cohort of 24 patients with thyroid sarcoidosis who were described in the literature in the 21st century and reported two additional cases of thyroid sarcoidosis.